Multiscale modelling of the radical-induced chemistry of acetohydroxamic acid in aqueous solution. Issue 46 (18th October 2022) - Conrad, Jacy K.; Pilgrim, Corey D.; Pimblott, Simon M.; Mezyk, Stephen P.; Horne, Gregory P.
Abstract : A comprehensive multiscale model determines the fundamental reaction mechanisms of the radical-induced degradation of acetohydroxamic acid in acidic aqueous solutions. Abstract : Acetohydroxamic acid (AHA) is a small organic acid with a wide variety of industrial, biological, and pharmacological applications. A deep fundamental molecular level understanding of the mechanisms responsible for the radical-induced reactions of AHA in these environments is necessary to predict and control their behaviour and elucidate their interplay with other attendant chemical species, for example, the oxidative degradation products of AHA. To this end, we present a comprehensive, multiscale computer model for interrogating the radical-induced degradation of AHA in acidic aqueous solutions. Model predictions were critically evaluated by a systematic experimental radiation chemistry investigation, leveraging time-resolved electron pulse irradiation techniques for the measurement of new radical reaction rate coefficients, and steady-state gamma irradiations for the identification and quantification of AHA degradation products: acetic acid, hydroxylamine, nitrous oxide, and molecular hydrogen, with formic acid and methane as minor products. Excellent agreement was achieved between calculation and experiment, indicating that this fundamental model can accurately predict the degradation pathways of AHA under irradiation in acidic aqueous solutions.